Intuisi Bagi Dunia Modern - Syarif, Edwin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2004)
This article reviews the book by David G. Myers titled “Intuition: Its Powers and Perils.” The book explains the existence of two influential schools of thought, rationalism emphasizing reason and empiricism focusing on sensory experience. Both have given rise to different disciplines of science. Rationalism, with its deductive method, has produced exact sciences, while empiricism, with its inductive method, has given birth to natural sciences. These two schools of thought—Rationalism and Empiricism—have shaped Western thinking for three centuries and have led to remarkable advances in science and technology.